La politique économique du Japon à l’égard du Canada - Langdon, Frank (Études internationales, 1985)
The article attempts to evaluate the balance of United Nations accomplishments in the field of peace and security since 1945. The first part deals with the elements one has to take into consideration to properly evaluate such performance. These are what the Organization ought to do (its objectives), what it could do (its means) and what it has done (the kinds of activities). In the second part, each one of these elements is examined. About the objectives, the article distinguishes between manifest and latent objectives and it argues that the first ones have not changed when the second ones have much changed. About the means, the article analyzes the powers given the UN and the way its principal organs exercise them. It traces the evolution of the roles of the Security Council, the General Assembly, the Secretary general and the International Court of Justice. Concerning the kinds of activities, the article uses a typology developed by H.K. Jacobson to argue that the main function of the UN is a "verbal" or informational one, that the normative function especially in its collective legitimization aspect is the second most important, that the rule supervisory function accounts or few activities, and, that the operational function is more developed than it may appear. The article concludes that the balance is a positive one pointing to the flexibility, the adaptability and the continued usefulness of the UN.